Development of a Knowledge Test to Assess Knowledge Level about Improved Dairy Farming Practices among Users and Non-users of e-Agriservice in Maharashtra - S.K. Wadkar; K. Singh; K.S. Kadian; Ritu Chakravarty; S.D. Argade (Journal of Agricultural Extension Management, 2017)
Effectiveness of JCT-enabled e-Agriservice - aAQUA (Almost All Questions Answered) with special reference to dairy farming, was assessed in Maharashtra. Ex-post-facto research design was followed. This paper presents the procedure to develop a knowledge index for users and non-users to assess impact in terms of knowledge gain about Improved Dairy Farming Practices (IDFPs) by availing the e-Agriservice. The study was conducted in randomly selected four districts of Maharashtra. A total of 3 7 items or questions were framed on breeding, feed-fodder, health care and management aspects of the IDFPs. It was found that the items with difficulty index between 0.25-0. 75, discrimination index above 20 and point bi-serial correlation significant at 5 per cent level of significance was selected for the knowledge test. Thus, a total of29 items from 37 items were retained in the knowledge test. The study would be useful for researchers and academicians to develop and use the knowledge test in other areas to measure knowledge level of dairy farmers